Human Endogenous Retrovirus K in the Crosstalk Between Cancer Cells Microenvironment and Plasticity: A New Perspective for Combination Therapy - Balestrieri, Emanuela; Argaw-Denboba, Ayele; Gambacurta, Alessandra; Cipriani, Chiara; Bei, Roberto; Serafino, Annalucia; Sinibaldi-Vallebona, Paola; Matteucci, Claudia (Frontiers in Microbiology, 2018)
Abnormal activation of human endogenous retroviruses (HERVs) has been associated with several diseases such as cancer, autoimmunity and neurological disorders. In particular, in cancer HERV activity and expression have been specifically associated with tumor aggressiveness and patient outcomes. Cancer cell aggressiveness is intimately linked to the acquisition of peculiar plasticity and heterogeneity based on cell stemness features, as well as on the crosstalk between cancer cells and the microenvironment. The latter is a driving factor in the acquisition of aggressive phenotypes, associated with metastasis and resistance to conventional cancer therapies. Remarkably, in different cell types and stages of development, HERV expression is mainly regulated by epigenetic mechanisms and is subjected to a very precise temporal and spatial regulation according to the surrounding microenvironment. Focusing on our research experience with HERV-K involvement in the aggressiveness and plasticity of melanoma cells, this perspective aims to highlight the role of HERV-K in the crosstalk between cancer cells and the tumor microenvironment. The implications for a combination therapy targeted at HERVs with standard approaches are discussed.